2000
DOI: 10.1007/s001980050001
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Variation in Premenopausal Bone Mineral Status: A Health Promotion Approach

Abstract: Bone loss prior to menopause may contribute to later risk of fracture due to osteoporosis. Women may be able to optimize premenopausal bone mass and/or prevent losses. Heredity, and possibly age at menarche (retrospectively determined), are unmodifiable risk factors and attention should therefore be directed to more amenable factors. Amenorrhea, low body weight, disordered eating, and smoking are modifiable risk factors. Vitamin D is not a factor for premenopausal women who receive incidental sun exposure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 293 publications
2
60
0
Order By: Relevance
“…The strong association between body weight and bone density has been documented in many prior studies of premenopausal women (54). Physical activity also was consistently predictive of higher BMD.…”
Section: Discussionmentioning
confidence: 56%
“…The strong association between body weight and bone density has been documented in many prior studies of premenopausal women (54). Physical activity also was consistently predictive of higher BMD.…”
Section: Discussionmentioning
confidence: 56%
“…A longitudinal study (followup for 10 y) on age-and menopause-related changes of BMD in 172 Japanese women aged 31-69 y showed that there was no significant decrease of BMD among women before menopause, but there was a significant decrease of BMD (Ϫ1.59%/y) in the early postmenopausal period compared with the premenopausal and late postmenopausal periods (18). The importance of primary prevention of osteoporosis by maximization of the peak BMD during the premenopausal years was highlighted in a recent review article (19). Because a decrease of BMD is inevitable after menopause, an essential part of the preventive strategy for minimizing the future risk of significant osteoporosis involves maximizing the peak BMD during the premenopausal period.…”
Section: Discussionmentioning
confidence: 99%
“…Gordon et al [19] found LTM to be the most important predictor of bone mineral in young adult females. Tudor-Locke [20] indicated that both LTM and FM contribute to increased compressive forces during skeletal loading but that LTM alone produces a tensile force on bone. In our study, LTMI showed a significant relation with the BMD of the left arm.…”
Section: Discussionmentioning
confidence: 99%
“…However, body weight is composed of fat mass (FM) and fat-free mass, and there is disagreement as to which has a greater effect on BMD [15][16][17][18][19][20]. VanItallie et al [21] demonstrated that FM and fat-free mass unadjusted by body height are not suitable for use in the evaluation of body composition, since the effects of body height on FM or fat-free mass differ.…”
Section: Introductionmentioning
confidence: 99%